Building Resilient Agricultural Communities: A Process for Addressing Mental Health Challenges in Agricultural Communities. Issue 1 (2nd January 2023) - Schossow, Megan; Kampa, Diane; Bender, Jeffrey
ABSTRACT: The impacts of stress on physical and mental health are increasingly salient, and understanding how occupational stress interacts with occupational health and safety will shape conditions and cultures for workers. The Upper Midwest Agricultural Safety and Health Center (UMASH) recognized a need to better understand occupational stressors and mental health outcomes in agriculture, and identify barriers to mental health care along with interventions to improve this system. UMASH hosted a one-day working forum that framed agricultural stress and poor mental health, and potential for interventions, for Minnesota farmers, agricultural workers, and their families. Building Resilient Agricultural Communities engaged a spectrum of stakeholders in agricultural work including: representatives of agricultural workers, farmers, health care, policy makers, and more. The forum further defined stressors and systemic barriers to health care for agricultural workers through presentations, panel discussion, that facilitated discussions and recommendations for intervention. Priority areas to focus outreach and engagement efforts, research, and screening are shared out, with reference to the continued outcomes and impact of this forum.